([tex]m_{1}[/tex], [tex]m_{2}[/tex], [tex]m_{3}[/tex]) = (3, -6, 3)
Explanation:
Given data,
[tex]p=m_{1} x^{2}+m_{2} x+m_{3}[/tex]
5 packets are delivered by channel, which was randomly taken.
0(P(0)), 1(P(1)), 2(P(2)), 3(P(3)), 4(P(4))
Bob receives are
(0,3) (1,0) (2,3) (3,0) (4,3)
P(0) = 3
P(1) = 0
P(2) = 3
P(3) = 0
P(4) = 3
The given equation is
[tex]p=m_{1} x^{2}+m_{2} x+m_{3}[/tex]
Solution:
[tex]p(0)=m_{1}(0)+m_{2}(0)+m_{3}[/tex] = 3
[tex]m_{3}[/tex] = 3
[tex]p(1)=m_{1}+m_{2}+m_{3}=0[/tex]
[tex]m_{1} + m_{2}[/tex] = - 3
[tex]m_{2} = -3 -m_{1}[/tex]
[tex]p(2)=4 m_{1}+2 m_{2}+m_{3}[/tex] = 3
[tex]4 m_{1}+2 m_{2}[/tex] = 0
[tex]2 m_{1}+m_{2}=0[/tex]
[tex]P(3)=9 m_{1}+3 m_{2}+m_{3}[/tex] = 0
[tex]3 m_{1}+m_{2}+3=0[/tex]
[tex]P(4)=16 m_{1}+4 m_{2}+m_{3}[/tex] = 3
[tex]4 m_{1}+m_{2}[/tex] = 0
From P(1) and P(2)
[tex]m_{2} = -3 -m_{1}[/tex]
[tex]2 m_{1}+m_{2}=0[/tex]
[tex]2 m_{1}-3-m_{1}=0[/tex]
-3 + [tex]m_{1}[/tex] = 0
[tex]m_{1}[/tex] = 3
[tex]m_{2}[/tex] = -6
([tex]m_{1}[/tex], [tex]m_{2}[/tex], [tex]m_{3}[/tex]) = (3, -6, 3)